4(8-3x)=32-8(x+2)

Simple and best practice solution for 4(8-3x)=32-8(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(8-3x)=32-8(x+2) equation:


Simplifying
4(8 + -3x) = 32 + -8(x + 2)
(8 * 4 + -3x * 4) = 32 + -8(x + 2)
(32 + -12x) = 32 + -8(x + 2)

Reorder the terms:
32 + -12x = 32 + -8(2 + x)
32 + -12x = 32 + (2 * -8 + x * -8)
32 + -12x = 32 + (-16 + -8x)

Combine like terms: 32 + -16 = 16
32 + -12x = 16 + -8x

Solving
32 + -12x = 16 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
32 + -12x + 8x = 16 + -8x + 8x

Combine like terms: -12x + 8x = -4x
32 + -4x = 16 + -8x + 8x

Combine like terms: -8x + 8x = 0
32 + -4x = 16 + 0
32 + -4x = 16

Add '-32' to each side of the equation.
32 + -32 + -4x = 16 + -32

Combine like terms: 32 + -32 = 0
0 + -4x = 16 + -32
-4x = 16 + -32

Combine like terms: 16 + -32 = -16
-4x = -16

Divide each side by '-4'.
x = 4

Simplifying
x = 4

See similar equations:

| x^3-6x+6x=0 | | 1.5X-(500+1X)=-100 | | 9x+18=26-3X | | 4x+(144+x)=180 | | 4-c+2=5c+1 | | 2a(a-5)+(a-5)= | | k^2+4=16 | | (3x-6)+10=10+4x | | 6=48*oz | | .4y-4=.33y | | -x^2-8x-9=0 | | e*80=2 | | 5=2x | | m*7=13 | | 16=w*4 | | c*9=6 | | -7-4r=-3(-7-8r) | | 7(x+2)=8-5(x-7) | | 8l+8-l=9-8 | | 3x-2x+10=10+5x-40 | | 4x+2=8-2x | | C^3-216=y | | 3(-7-6x)-8=37+4x | | 5+2x=7(x+2)-6(x-2) | | x^2+21x+59=0 | | -(3-m)=-(4m+3) | | 100/566=1/9 | | -(x+1)+2=2x+1-3x | | 3(x+2)=9x+3-6x+3 | | 900/566= | | 10x-9=21+2x+3x | | -7a-(-2b)= |

Equations solver categories